Ancient DNA reveals potentially toxic cyanobacteria increasing with climate change. (1st February 2023) - Zhang, Jifeng; Shi, Kun; Paerl, Hans W.; Rühland, Kathleen M.; Yuan, Yanli; Wang, Rong; Chen, Jie; Ge, Mengjuan; Zheng, Lingling; Zhang, Zhiping; Qin, Boqiang; Liu, Jianbao; et al.
Highlights: SedaDNA metabarcoding revealed cyanobacterial community over past ∼100 years. A steady increase in toxic cyanobacteria during past 30 years in Lake Taihu. Climatic warming explains the increasing trend of toxic cyanobacteria. Recent climate change is exacerbating the harmful effects of toxic cyanobacteria. Abstract: Cyanobacterial blooms in freshwater systems are a global threat to human and aquatic ecosystem health, exhibiting particularly harmful effects when toxin-producing taxa are present. While climatic change and nutrient over-enrichment control the global expansion of total cyanobacterial blooms, it remains unknown to what extent this expansion reflected cyanobacterial assemblage due to the scarcity of long-term monitoring data. Here we use high-throughput sequencing of sedimentary DNA to track ∼100 years of changes in cyanobacterial community in hyper-eutrophic Lake Taihu, China's third largest freshwater lake and the key water source for ∼30 million people. A steady increase in the abundance of Microcystis (as potential toxin producers) during the past thirty years was correlated with increasing temperatures and declining wind speeds, but not with temporal trends in lakewater nutrient concentrations, highlighting recent climate effects on potentially increasing toxin-producing taxa. The socio-environmental repercussions of these findings are worrisome as continued anthropogenic climate change may counteract nutrient amelioration efforts in this critical freshwater resource. Graphic abstract: Image, graphical abstract